Archaeological research a brief introduction - Peregrine, Peter N. (Peter Neal) 1963- (London Routledge, 2017)
This updated edition of Archaeological Research introduces the basic methods of archaeological research, including data collection, analysis, interpretation, as well as a consideration of the state of archaeology today. New to the Second Edition is updated information on geographic information systems and remote sensing strategies, and a greatly expanded discussion of practices in cultural resource management archaeology. This popular, concise textbook explores various research methods, analytical techniques, legal and ethical issues facing archaeologists; includes discussions of the archaeological process and record, sampling and research design, survey and excavation methods and strategies, recordkeeping, analysis, archaeological dating, presenting results, and research opportunities; is an excellent text for undergraduate students in basic archaeology courses, field methods courses, and field schools.
Includes bibliographical references and index.
Keywords: Archaeology -- Methodology